A review of Aconiti Lateralis Radix Praeparata (Fuzi) for kidney disease: phytochemistry, toxicology, herbal processing, and pharmacology - Wu, Ziyang; Qian, Jiawen; Feng, Chenhang; Chen, Zhouqi; Gao, Xiangfu; Liu, Yang; Gao, Yuancheng (Frontiers in Pharmacology, 2024)
Background: Aconiti Lateralis Radix Praeparata, commonly known as Fuzi in traditional Chinese medicine (TCM), is widely utilized in clinical practice despite its inherent toxicity. Since ancient times, TCM practitioners have explored various processing techniques to broaden its clinical applications and enhance its safety profile. This review aims to summarize the effects of processing on the chemical composition, toxicity, and pharmacological properties of Fuzi, as well as investigate potential underlying mechanisms. Methods: Data on phytochemistry, toxicology, pharmacology, and processing methods of Fuzi were gathered from the literature of electronic databases, including Web of Science, PubMed, and CNKI. Results: Fuzi contains over 100 kinds of chemical compounds, including alkaloids, flavonoids, and polysaccharides, among which alkaloids are the main active compounds. Diester-diterpenoid alkaloids are the main contributors to Fuzi’s toxicity and have side effects on some organs, such as the heart, liver, kidneys, nervous system, and reproductive system. The chemical composition of aconite, particularly its alkaloid content, was changed by hydrolysis or substitution reaction during processing to enhance its efficacy and reduce its toxicity. Salted aconite could enhance the therapeutic efficacy of Fuzi in treating kidney diseases and influence its pharmacokinetics. Conclusions: Processing plays an important role in increasing the efficiency and decreasing toxicity of aconite. Further studies are needed to elucidate the changes of aconite before and after processing and the underlying mechanisms of these changes, thereby providing evidence for the clinical safety of drug use.